DAMPAK PENGGUNAAN MEDIA DIGITAL TERHADAP PERKEMBANGAN PERILAKU SOSIAL ANAK USIA 7 TAHUN - Delfira Thalita Asri, - (2020)
This research is motivated by findings regarding the symptoms associated with technological development in children, especially at 7 years of age, on children's behavior that can threaten their social life, such as ignorance, difficulty socializing, rarely communicating and interacting with other people. The purpose of this study was to determine the description regarding 1) behavioral symptoms that appear in children using digital media, 2) mentoring parents in accompanying children when using digital media, and 3) behavior of children using digital media after mentoring. This research was conducted in an effort to reveal that the use of digital media currently has an influence on children's social behavior towards those around them. This research is a qualitative research with a case study method. The research subject is one of the children who are really active users of their digital media. The data collection technique was done by means of observation, interviews, questionnaires, literature and documentation. The results showed that 1) the behavioral symptoms that appeared in the subject so far from the use of digital media were lack of courage, rebellion, less independence, indifference and passivity, 2) parental assistance in accompanying children when using digital media was high, 3) children's behavior After mentoring digital media users, there are developments in children's courageous behavior and initiative.